ملامح الهوية الإسلامية المستقاة من كتاب "صور من حياة الصحابة: Features of Islamic Identity Derived from the Book “Scenes from the Companions Lives“ - Samya Noor,; Dr. Khansa Al-Jaje, (Al Manhal Research Journal, 2025)
A person's features consist of traits and characteristics that come together to distinguish that individual from others, by which they are recognised. Similarly, the Islamic identity has features and signs that set it apart from other identities that have existed on Earth since the beginning of mankind and the ongoing struggle between truth and falsehood. Islam does not confine itself to acts of worship between a person and God alone. Still, it is a comprehensive religion that has a stance and ruling on every aspect of individual, social, and international life. As Muslims, we need to preserve our identity and protect it from dissolving in the overwhelming tide of globalisation in our present day. We cannot succeed in this unless we know its features and defining characteristics that distinguish it from other identities. This research aims to identify and extract features of the Islamic identity that were not merely recorded as theories in books, but were behaviours, actions, and real-life situations that occurred in the real world. The writer, Abdul Rahman Ra’fat Al-Basha intended to make these features evident and clear to the rising generation by compiling incidents and stories involving a large group of the noble Companions (may Allah be pleased with them). We found that, in their entirety, they form features of the Islamic identity that help Muslim youth understand their religion and its impact on souls, reveal to them the greatness of this identity, instill in them a sense of honor, dignity, and pride in belonging to this great religion, and pave the way for them to hold firmly to the features of this identity and follow its path.